(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Beside infections, foreign body incidences are amongst the most frequently encountered pathologies in Head and neck region. Accidental foreign body with metallic in nature can be associated with dangerous consequences. We present a case of a man who presented with an unusual foreign body, a pellet of balloon shooting gun which get impacted at anterior aspect of lower neck while playing and was not noticed till three days. Unnoticed foreign body are more harmful and related with complications. Radiological investigation is the tool to diagnose it properly apart from clinical examination. Head and neck region is known for its complex anatomy and to deal with it one has to sound knowledge of it.